Playing Tetris with porphyrins: the synthesis of porphyrinic materials for self-sssembly studies - Hames, Tim (2016)
This thesis focuses on the synthesis of porphyrinic materials for self-assembly studies. It begins with the synthesis of a large number of ‘building block’ molecules, terminated with bromo-, alkyne- and TMS- groups. These molecular building blocks are combined to form porphyrin compounds also terminated with bromo- alkyne- and TMS- groups at carefully selected positions. A series of porphyrin arrays inspired by the computer game Tetris was designed to be synthesised from these porphyrin units. The Tetris compounds are comprised of four square-like tetraphenylporphyrin (TPP) units, linked together with alkyne bridges to create arrays shaped like the T, I, L/J, S/Z and O Tetriminos. The NMR spectroscopy of the Tetris compounds is thoroughly explored to highlight the slight structural differences between the molecules. The synthesis of two bromoaryl-terminated porphyrin dimers for ultimate incorporation into covalent organic frameworks (COFs) is also described. The X-ray diffraction data collected showed that crystals grown were of trifluoroacetic acid (TFA) salts of the target compounds. The presence of the TFA anions resulted in significant distortion of the porphyrin ring which is described in full. Finally, the synthesis of a series of poly(acetylene) anthracene dimer compounds that have potential use in the field of organic electronics has also been explored. The electrochemical and fluorescence properties of the molecules across the series are investigated and the crystal structures are described.